PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN GENERATIF - M Rizky Tama Putra; Risda Intan Sistyawati; Rohman Rohman (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
The very low learning outcomes of students, especially in mathematical communication skills regarding teaching and learning activities, is one source of problems in learning that must be overcome by every teaching staff. This research aims to see an increase in the mathematics communication learning outcomes of students who are taught using a generative model. Classroom Action Research (PTK) or Classroom Action Research (CAR) is this type of research. The subjects in this research were 30 class VIII students at a junior high school in the city of Palembang. The research flow uses the Kemmis and Mc flow. Taggart, the stages in this research are planning, action, observation and reflection which were carried out in two cycles. Data collection took the form of tests to measure mathematical communication skills and questionnaire sheets used to determine learning implementation. From the results of data analysis, the average student learning outcome in cycle I was 72.85 with a student completion percentage of 60%, the average student learning outcome in cycle II rose to 77.65 with a student completion percentage of 83.33%. Meanwhile, the results of the observation sheet show that the implementation of learning activities is going well. The conclusion is that mathematics learning taught by generative models can improve students' mathematical communication skills.